2018
DOI: 10.1017/neu.2018.26
|View full text |Cite
|
Sign up to set email alerts
|

Selective serotonin reuptake inhibition increases noise burst-induced unconditioned and context-conditioned freezing

Abstract: ObjectiveWhereas long-term administration of selective serotonin reuptake inhibitors (SSRIs) is effective for the treatment of anxiety disorders, acute administration of these drugs may exert a paradoxical anxiogenic effect. The aim of the present study was to explore the possible effect of an SSRI in situations of unconditioned or limited conditioned fear.MethodsMale Sprague Dawley rats were administered a single dose of an SSRI, escitalopram, before acquisition or expression of context conditioned fear, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The chamber was enclosed by a sound-attenuating cubicle in which a constant 60-dB white background noise was delivered during all experimental sessions. Seven days later, the rats were re-exposed to the conditioning chamber for assessment of context-conditioned freezing calculated by automatic scoring of video recordings (immoblity >1 second) and presented as the percentage (%) of the 5-minute test that the animal spent immobile ( Anagnostaras et al, 2010 ; Hagsater et al, 2019 ). For any rat showing immobility, gross observation was applied to confirm that the animal displayed typical signs of freezing, that is, rigged tail, arched back, erected fur, and retracted ears ( Riess, 1945 ; Brandao et al, 2008 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chamber was enclosed by a sound-attenuating cubicle in which a constant 60-dB white background noise was delivered during all experimental sessions. Seven days later, the rats were re-exposed to the conditioning chamber for assessment of context-conditioned freezing calculated by automatic scoring of video recordings (immoblity >1 second) and presented as the percentage (%) of the 5-minute test that the animal spent immobile ( Anagnostaras et al, 2010 ; Hagsater et al, 2019 ). For any rat showing immobility, gross observation was applied to confirm that the animal displayed typical signs of freezing, that is, rigged tail, arched back, erected fur, and retracted ears ( Riess, 1945 ; Brandao et al, 2008 ).…”
Section: Methodsmentioning
confidence: 99%
“…While SSRIs are first-line treatment for a number of anxiety disorders ( Eriksson and Humble, 1990 ; Nutt, 2005 ), initially these drugs may, on the contrary, elicit or augment anxiety ( Sinclair et al, 2009 ; Naslund et al, 2017 ). Similarly, in fear-conditioned rats, both freezing-dampening ( Hashimoto et al, 1996 ; Inoue et al, 1996b ; Santos et al, 2006 ; Montezinho et al, 2010 ) and freezing-promoting ( Burghardt et al, 2007 ; Montezinho et al, 2010 ; Pettersson et al, 2015 ; Hagsater et al, 2019 ) effects of acute exposure to an SSRIs have been reported. While the reasons for these differences between studies remain obscure, the capability of an SSRI to exert both an anxiogenic-like and an anxiolytic-like influence on the expression of fear-conditioned freezing suggests that the enhanced extracellular levels of serotonin obtained by acute serotonin reuptake inhibition may activate both freezing-promoting and freezing-dampening pathways, the behavioral outcome being dependent on the relative impact of these—and possibly on the relative impact of different postsynaptic receptor subtypes—in the experimental situation at hand.…”
Section: Introductionmentioning
confidence: 92%
“…Generally, they are considered to be equally effective in many cases, albeit with some specific differences ( 22 , 23 ). Responses to SSRI are thought to be dependent on baseline levels of performance and serotonergic function ( 95 , 117 , 118 ), while individuals with anxiety and depression are often found to have decreased prefrontal activation activity during effortful emotion regulation strategies ( 18 , 98 , 119 ).…”
Section: Discussionmentioning
confidence: 99%
“…An overexpression of 5-HT2C receptors was found in the prefrontal cortices of some suicide victims, which suggests a potential pathogenic role of 5-HT2C in depression and anxiety. Moreover, acute SSRI intake may precipitate anxiety through the activation of 5-HT1A autoreceptors and 5-HT2C receptors (Stamm et al, 2017;Hagsäter et al, 2019). Agomelatine is a novel antidepressant that functions as a 5-HT2C receptor antagonist and At present, it is mainly used in the treatment of severe chronic depression.…”
Section: -Ht a Receptormentioning
confidence: 99%